Yael Bartana and Post‐traumatic Culture: Utopian Reversibility and the Case of Polish National Melancholia. (21st November 2012) - Sclodnick, Hilary
ABSTRACT Mary Koszmary (2007) is one short film from a trilogy by Israeli artist Yael Bartana, which centers on the exhortations of a Polish radical politician calling for the comeback of three million Jews to Poland. This Polish trilogy focuses a lens, both artistic and psychoanalytic, on the place of the unbearable in the human psyche, reality which must be neither attended to nor acknowledged. The example of the unbearable and inassimilable which Bartana chooses is Poland's complicity and cooperation with the murder of her Jews. The Jewish genocide roughly seventy years ago involves inassimilable shame and guilt, defended against by national repression, denial and fetishistic dissociation. Bartana imagines a symptom in today's generation which both refutes and repeats the history enacted by their grandparents. Bartana assumes a deep‐set collective trauma manifesting bizarrely two generations later and conjures an unflinching picture of why failure to come to terms with and to mourn traumatic losses is relentlessly a problem in human history. The purpose of this paper is to explore the symptoms of the intergenerationally transmitted collective trauma as these symptoms translate from those of the individual traumatic condition in order to deepen our understanding of the effects of both individual and collective trauma when unresolved over time and particularly over generations. The first step toward healing is to acknowledge. Bartana's film sets up the opportunity for acknowledgment shining a clear cool light on so many modes of obfuscation. Copyright © 2012 John Wiley & Sons, Ltd.